Designing Timber Harvesting to Enhance New Zealand Falcon Populations. Issue 3 (18th February 2021) - Horikoshi, Chifuyu; Battley, Phil F.; Minot, Edward O.
ABSTRACT: Previous breeding‐season studies of threatened New Zealand falcons ( Falco novaeseelandiae ) in plantation forests have suggested that falcons benefit when harvesting creates a mosaic of differently aged stands, especially where young and mature tree stands are adjacent. Thus, changes in the rate and pattern of harvesting may affect habitat heterogeneity by altering the size and distribution of forest patches. We sought to determine guidelines for harvesting that would most benefit falcons by increasing the carrying capacity of the forest for falcons. We used radio‐tracking to determine the home‐range sizes of non‐breeding falcons over 3 seasons and compared winter home‐range overlap in the most‐selected land cover types by falcons (mature‐young edges and open patches) with other land cover types. The distribution of open patches and edges between mature stands and recently cleared areas affected falcon home ranges, home‐range overlap, and the likelihood of nesting. Specifically, home ranges were smaller as the density of edges and percentage of open patch increased, and there was greater home‐range overlap between individuals in the most‐selected land cover types. Numbers of falcons decreased as the size of open patches increased, concomitant with a decrease in edge size, the number of edge borders, and the number of open patches. The likelihood of nesting also decreased as open patch size increased. Our results indicate that smaller open patches spread through a forest, maximizing the amount of mature‐young edges, will favor smaller home ranges and therefore potentially greater numbers of falcons. We recommend harvesting protocols that ensure that open patches (0–3‐yr‐old stands) are <4 km 2 in size and retain at least small stands of mature pine to maintain a high density of edges. Similar protocols may increase the carrying capacity for other species occurring in managed systems involving fragmented landscapes or small reserves. © 2021 The Wildlife Society. Abstract : For New Zealand falcons in a managed plantation forest in New Zealand, the abundance and distribution of open patches and edge determines habitat use, breeding site selection, and home‐range size. Well‐designed logging protocols developed and integrated into the commercial pine forestry management regimens in New Zealand could be adapted to other situations where threatened species exhibit similar forest structure preferences.